2002
DOI: 10.2139/ssrn.307091
|View full text |Cite
|
Sign up to set email alerts
|

Small Business in Russia: A Case Study of St. Petersburg

Abstract: The reasons why small business development has been disappointing in Russia compared with other transition countries such as Poland and the Czech Republic are here analyzed. It is, however, suggested that the picture may not be so gloomy as official statistics suggest. As far as St. Petersburg is concerned, it has witnessed an exceptional-by Russian standards-growth in this sector in the 1990s, although it still trails compared with Moscow. This, despite the lack of support from the local administration and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As a result he said, they would increase sales but do so slowly, moderately; to do so quickly was to “quickly die” […] “the most important […] thing for us is the people, the experience and staff. And they cannot grow very very quick.” The absence of key business skills and experience in Russia (compared with Russia's Eastern European counterparts) has been attributed to a weak tradition of entrepreneurship, as well as a long period of Communist rule in the country (Kihlgren, 2002). Furthermore, it has been argued that the skills base developed in Russia during Communist times was not readily transferable to those industries that would later come to characterise the new private sector (Clarke and Metalina, 2000).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result he said, they would increase sales but do so slowly, moderately; to do so quickly was to “quickly die” […] “the most important […] thing for us is the people, the experience and staff. And they cannot grow very very quick.” The absence of key business skills and experience in Russia (compared with Russia's Eastern European counterparts) has been attributed to a weak tradition of entrepreneurship, as well as a long period of Communist rule in the country (Kihlgren, 2002). Furthermore, it has been argued that the skills base developed in Russia during Communist times was not readily transferable to those industries that would later come to characterise the new private sector (Clarke and Metalina, 2000).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Russia was considered a suitable location for empirical research because barriers to business formation and growth are prevalent in this context and may be to blame for comparatively low levels of small business development (e.g. OECD, 2009; Doern, 2008; Estrin et al , 2006; CEFIR, 2005; Kihlgren, 2002; Polonsky, 1998; Frye and Shleifer, 1997). It is also the case that Russia is a country in transition and very little is known about the behaviour of entrepreneurs in this context (Bruton et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several studies conducted in Russia on entrepreneurship and small business development have identified specific institutional barriers to entrepreneurial behaviour that we contend are uniquely social in nature, involving interactions between entrepreneurs and state officials; they include but are not limited to a lack of transparency in legislation, the high volume of and frequent changes in legislation (Balcerowiczet al, 1999), high taxation (Aidis and Mickiewicz, 2004; Barkhatova, 2000; Bartlett and Rangelova, 1997; Bohatá and Mládek, 1999; Dadashev et al, 2003; Danis and Shipilov, 2002; Shama, 2001), frequent inspections by different state agencies, 5 bureaucracy and bribe taking by officials (Aidis et al, 2008; CEFIR, 2005; Frye and Shleifer, 1997; Kuznetsov and Kuzentsova, 2003; Yakovlev, 2006; Zamulin, 2004). These institutional barriers, in conjunction with a general disregard for/suspicion of small businesses by the government historically (Chepurenko and Vilensky, 1996) in favour of larger enterprises (Kihlgren, 2003; Randall, 2001), might explain in part why entrepreneurial activity in the country is limited (Estrin et al, 2006; Kihlgren, 2002, 2003; McMillan and Woodruff, 2002; OECD, 2009; Polonsky, 1998; Seawright et al, 2008) and has neglected to fulfil its potential (Acs and Audretsch, 1993; Johnson and Loveman, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Russia, we suggest, is a useful context in which to develop a model of social barriers to entrepreneurial action. The country’s comparatively low level of entrepreneurial activity (Estrin et al, 2006; Kihlgren, 2002; OECD, 2009; Seawright et al, 2008) has been attributed, in part, to an underdeveloped and hostile institutional environment (Aidis et al, 2008; CEFIR, 2005) within which entrepreneurs routinely have to confront different forms of corruption and racketeering in order to develop their businesses (Frye and Shleifer, 1997; Infante and Smirnova, 2009; Kuznetsov and Kuznetsova, 2003; Yakovlev, 2006). As such, it provides what Bamberger and Pratt (2010) have termed an ‘unconventional research context’.…”
Section: Introductionmentioning
confidence: 99%
“…We focus our attention on the social interactions between entrepreneurs and state officials in Russia-which was regarded as a suitable context for research because the Russian business environment is often unpredictable and hostile to entrepreneurship. This has been blamed partly on bureaucratic inefficiencies and related state corruption, which erect numerous barriers to entrepreneurship (Aidis, Estrin, & Mickiewicz, 2008;Frye & Shleifer, 1997;Yakovlev, 2006) and, in turn, result in comparatively low levels of entrepreneurial activity (e.g., Center for Economic and Financial Research, 2005;Estrin, Meyer, & Bytchkova, 2006;Kihlgren, 2002;Organisation for Economic Co-operation and Development, 2009;Polonsky, 1998). Thus, Russia provides a rich context for studying entrepreneurial emotions.…”
Section: Introductionmentioning
confidence: 99%